Direito fundamental à saúde: construindo alguns pressupostos para uma atuação preventiva - Costa, Edson Silva da (Universidade do Vale do Rio dos Sinos, 2012)
The right to health is a fundamental right, formal and materially constitutional, but, despite its constitutional provision, as the diction of Federal Constitution art. 196 a “right of all and duty of the State, warranted by social and economic politics that aimed at reducing the risk of disease and other hazards and at universal and equal access to actions and services for its promotion, protection and recovery”, in practice it is not achieved. This thesis outlines a history of human rights and fundamental concepts and health history forms and interventional demonstrates the ineffectiveness of protecting the fundamental right to health by current models of intervention, indicates that the main causes of the crisis in health, demonstrates the role of principals in the implementation of the fundamental right to health, especially the principle of prevention, highlights the fundamental right, presents new perspectives on health, the implementation of preventive measures and the challenges to be overcome for their installation, to , ultimately to build assumptions a preventive action in health for achieving the fundamental right to healt.
Keywords: Direito fundamental à saúde; Políticas públicas; Inefetividade da proteção ao direito à saúde; Princípios e medidas preventivas; Fundamental right to health; Public policies; Ineff ectiveness of protecting the right of health; Principles and prev entive Measures; ACCNPQ::Ciências Sociais Aplicadas